Enhancement of data transmission using optimized multi-cell approach in 5G backhaul wireless mesh network - Nirmalkumar S Benni; Sunilkumar S Manvi (Institute of Advanced Engineering and Science, 2019)
The millimeter wave (mmWave) band and its usage has taken an attention in this 5G creation as its implementation can provide ultra-high speed data transmission in wireless network. This is much better than the centimeter wave-band as it has limitations on the bandwidth usage. While considering the 5G networking with the backhaul-topologies, the network and user-equipment performance depends on the selection of serving receiving nodes (RNs) of the user-equipment (UE). Therefore, the algorithms that reduces the complexity of the UE association and the backhaul traffic-routing must be chosen, which thereby maximizes the efficiency of the spectrum and energy of network. The modifications are done to the Multicellular local solution (McLS)approach, which leads to our proposed algorithm that is, improved against the channel information estimation-errors. The optimized multi-cell approach (OMcA) is formed by combining the improved-parameter, the pre-coder, mean square error (MSE) weighted-variable and receive filter. The proposed OMcA is compared with some other existing technique in order to evaluate the performance in terms of sum rate (SR).